DAKWAH IN THE STUDY OF RELIGIOUS MODERATION - Uswatun Hasanah (Alfuad: Jurnal Sosial Keagamaan, 2021)
Considering Indonesia as a plural country consisting of various races, ethnicities, religions and languages. So the theme of religious moderation is considered important to be discussed and researched by academics in particular. However, this paper wants to see how the Messenger of Allah actualized the context of religious moderation in his da'wah, either da'wah in Mecca or da'wah in Medina. The results of this study indicate that the Prophet succeeded in practicing the concept of religious moderation both while he was in Mecca and while in Medina, he managed to live side by side with people from various ethnic backgrounds, tastes, religions and cultures in a peaceful, harmonious, and prosperous manner, especially while he was in Medina. Not only that, he also succeeded in making Islam the majority religion in Arabia at that time. This research is a qualitative research, the type of literature review the data obtained through books and articles or journals that are relevant to this research. The data that has been collected is described in detail and structured.